Clinico-pathological characteristics and outcomes of nephrology adolescents and young adults in Cape Town: a single centre study - Barday, Zibya (Department of Medicine, 2023)
Background Adolescents and young adults [AYA] are important users of the nephrology health care services. Worldwide, there is a paucity of data on AYA kidney disease and outcomes. This study evaluates kidney outcomes, survival and challenges faced by AYA in a South African setting. Methods This 5-year retrospective study included AYA [aged 10-24] with chronic kidney disease, at a tertiary nephrology service in South Africa. Descriptive analysis characterised the aetiology of kidney disease. A comparative analysis of baseline characteristics, outcomes and social challenges were performed between patients attending a dedicated AYA clinic and those attending the standard adult clinics [non-AYA clinics]. Primary composite outcome assessed included doubling of creatinine, reduction of eGFR >40%, end-stage kidney disease and death. Logistic regression evaluated associations between relevant variables, death and lost to follow up [LTFU]. Results The total AYA cohort consisted of 292 patients, 111 (38.0%) attended the AYA clinic and 181 (62.0%) the non-AYA clinics. The main aetiologies of disease were glomerular 212 (72.6%), congenital anomalies of the urinary tract 31 (10.6%), and hereditary conditions 24 (8.2%). There was a significantly lower mortality (p=0.007) and reduction in LTFU (p=0.012) in the cohort attending the AYA clinic. A statistically significant composite outcome (p=0.018), with improved kidney survival was found in the AYA clinic group. High proportions of nonadherence (33.9%) and substance use (25.0%) was demonstrated in both cohorts. Conclusion This study adds to the dearth of literature on AYA kidney disease. A dedicated nephrology AYA clinic is shown to have lower mortality, less LTFU and improved kidney outcomes, which is essential in a resource-limited setting where access to kidney replacement therapy is restricted.